2023
DOI: 10.5194/essd-15-4901-2023
|View full text |Cite
|
Sign up to set email alerts
|

CLARA-A3: The third edition of the AVHRR-based CM SAF climate data record on clouds, radiation and surface albedo covering the period 1979 to 2023

Karl-Göran Karlsson,
Martin Stengel,
Jan Fokke Meirink
et al.

Abstract: Abstract. This paper presents the third edition of The Satellite Application Facility on Climate Monitoring's (CM SAF) cloud, albedo, and surface radiation dataset from advanced very-high-resolution radiometer (AVHRR) data, CLARA-A3. The content of earlier CLARA editions, namely cloud, surface albedo, and surface radiation products, has been extended with two additional surface albedo products (blue- and white-sky albedo), three additional surface radiation products (net shortwave and longwave radiation, and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…The differences between CN_WMO and Clim40 shown in Figures 1 and 3 for the total and low cloud fraction, respectively, are noteworthy. Previous studies have shown that the global cloud cover is generally decreasing when the trends are computed over the last forty years [21,23,25,26,48]. The decrease has mainly occurred over the sub-tropical to mid-latitudes in both hemispheres.…”
Section: Total and Low Cloud Fractionmentioning
confidence: 90%
See 4 more Smart Citations
“…The differences between CN_WMO and Clim40 shown in Figures 1 and 3 for the total and low cloud fraction, respectively, are noteworthy. Previous studies have shown that the global cloud cover is generally decreasing when the trends are computed over the last forty years [21,23,25,26,48]. The decrease has mainly occurred over the sub-tropical to mid-latitudes in both hemispheres.…”
Section: Total and Low Cloud Fractionmentioning
confidence: 90%
“…In this study, we use the data from the third edition of the CM SAF cLoud, Albedo and surface RAdiation dataset from AVHRR data, CLARA-A3 [21]. This climate data record has a rich history of dedicated, continuous developments and improvements dating back to its beginning 25 years ago in the framework of EUMETSAT's Satellite Application Facility on Climate Monitoring [46].…”
Section: Satellite-based Cloud and Radiation Climate Data Recordmentioning
confidence: 99%
See 3 more Smart Citations